Climate Change and Human Health: Strategies for Building Resilient Healthcare Systems - Irene Florensia Situmeang; Samantha Gonzales; Luis Santos (Yayasan Adra Karima Hubbi, 2025)
Climate change has intensified environmental stressors that directly and indirectly threaten human health, including rising temperatures, extreme weather events, vector borne disease expansion, and disruptions to food and water security. Healthcare systems worldwide face increasing pressure as climate-related hazards exacerbate morbidity and mortality, revealing systemic vulnerabilities in infrastructure, workforce capacity, and emergency preparedness. This study aims to identify strategic approaches for strengthening healthcare system resilience in the face of climate change by examining adaptive, organizational, and technological interventions. A mixed methods design was employed, combining systematic literature analysis with case based evaluations of climate adaptation initiatives implemented across multiple regions. The findings show that integrated climate health surveillance, climate resilient infrastructure, workforce training, and digital early-warning systems are among the most effective strategies for enhancing resilience. The results also highlight that governance coordination and equitable resource allocation significantly shape adaptive capacity. The study concludes that building resilient healthcare systems requires a multisectoral approach that embeds climate risk assessment into health planning, expands adaptive technologies, and prioritizes vulnerable populations.